Ground reaction force and centre of pressure in alpine skiing carved turn - Keränen, T.; Valieata, R.; Linden, P. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: The carving turn is the basic move of the modern alpine skiing technique. It can be identified by the skier's open position, which allows effective use of the knee joints. The more weight a skier transfers to one or both skis, the better he/she grips during the turn. The purpose of this study was to determine the force level and area of the centre of pressure under the feet during carved turn among male alpine skiers.